Pain, Spirituality, and Meaning Making: What Can We Learn from the Literature? - Lysne, Carol J. (Religions, 2011)
Religion and spirituality are two methods of meaning making that impact a person’s ability to cope, tolerate, and accept disease and pain. The biopsychosocial-spiritual model includes the human spirit’s drive toward meaning-making along with personality, mental health, age, sex, social relationships, and reactions to stress. In this review, studies focusing on religion’s and spirituality’s effect upon pain in relationship to physical and mental health, spiritual practices, and the placebo response are examined. The findings suggest that people who are self efficacious and more religiously and spiritually open to seeking a connection to a meaningful spiritual practice and/or the transcendent are more able to tolerate pain.